Weekly versus basic smoking cessation support in primary care: a randomised controlled trial. - Aveyard, P; Brown, K; Saunders, C; Alexander, A; Johnstone, E; Munafò, MR; Murphy, M (2007)
BACKGROUND: There is insufficient and conflicting evidence about whether more intensive behavioural support is more effective than basic behavioural support for smoking cessation and whether primary care nurses can deliver effective behavioural support. METHODS: A randomised controlled trial was performed in 26 UK general practices. 925 smokers of >or=10 cigarettes per day were randomly allocated to basic or weekly support. All participants were seen before quitting, telephoned around quit day, and seen 1 and 4 weeks after the initial appointment (basic support). Participants receiving weekly support had an additional telephone call at 10 days and 3 weeks after the initial appointment and an additional visit at 2 weeks to motivate adherence to nicotine replacement and renew quit attempts. 15 mg/16 h nicotine patches were given to all participants. The outcome was assessed by intention to treat analyses of the percentage confirmed sustained abstinence at 4, 12, 26 and 52 weeks after quit day. RESULTS: Of the 469 and 456 participants in the basic and weekly arms, the numbers (%) who quit and the percentage difference were 105 (22.4%) vs 102 (22.4%), 0.1% (95% CI -5.3% to 5.5%) at 4 weeks, 66 (14.1%) vs 52 (11.4%), -2.6% (95% CI -6.9% to 1.7%) at 12 weeks, 50 (10.7%) vs 40 (8.8%), -1.9% (95% CI -5.7% to 2.0%) at 26 weeks and 36 (7.7%) vs 30 (6.6%), -1.1% (95% CI -4.4% to 2.3%) at 52 weeks. CONCLUSIONS: The absolute quit rates achieved are those expected from nicotine replacement alone, implying that neither basic nor weekly support were effective. Primary care smoking cessation treatment should provide pharmacotherapy with sufficient support only to ensure it is used appropriately, and those in need of support should be referred to specialists.